Regular Intake of Pistachio Mitigates the Deleterious Effects of a High Fat-Diet in the Brain of Obese Mice - Domenico Nuzzo; Giacoma Galizzi; Antonella Amato; Simona Terzo; Pasquale Picone; Laura Cristaldi; Flavia Mulè; Marta Di Carlo (MDPI AG, 2020)
Obesity has been associated with neurodegeneration and cognitive dysfunctions. Recent data showed that pistachio consumption is able to prevent and ameliorate dyslipidemia, hepatic steatosis, systemic and adipose tissue inflammation in mice fed a high-fat diet (HFD). The present study investigated the neuroprotective effects of pistachio intake in HFD mice. Three groups of mice were fed a standard diet (STD), HFD, or HFD supplemented with pistachio (HFD-P) for 16 weeks. Metabolic parameters (oxidative stress, apoptosis, and mitochondrial dysfunction) were analyzed by using specific assays and biomarkers. The pistachio diet significantly reduced the serum levels of triglycerides and cholesterol in the HFD model. No difference was observed in the index of insulin resistance between HFD and HFD-P. A higher number of fragmented nuclei were found in HFD cerebral cortex compared to STD and HFD-P. A decrease in reactive oxygen species, singlet oxygen and phosphorylated extracellular signal-regulated kinase, and an increase of superoxide dismutase 2 and heme oxygenase expression were found in the brains of the HFD-P samples compared to HFD. Furthermore, the impaired mitochondrial function found in HFD brain was partially recovered in HFD-P mice. These results suggest that the regular intake of pistachio may be useful in preventing obesity-related neurodegeneration, being able to reduce both metabolic and cellular dysfunctions.